2022
DOI: 10.3390/pathogens11060669
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Anti-Theileria equi Antibodies in Horses from Three Geographically Distinct Areas of Romania

Abstract: Equine piroplasmosis (EP) is an endemic tick-borne disease found in most countries around the world. It affects all species of Equidae, and it is caused by Theileria equi, Babesia caballi and T. haneyi. The research herein is the second study on the prevalence of piroplasms in Romania conducted in the past two decades. The aim of this study was to assess the seroprevalence of anti-Theileria equi antibodies and the geographical distribution of this disease in the southwest, west, and northwest regions of Romani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…equi have been reported in horses in the Netherlands (0.0%/1.6%) [16], Poland (-/7.2%) [17], Hungary (0.0%/15.1%) [18], Romania (2.2%/20.3%) [19], the central Balkans (2.1%/22.5%) [20], Croatia (3.6%/13.2%) [21], and Italy (10.3%/70.3%) [22]. There have also been reports of seropositive horses in central Germany (0.3%/6.1%) [23], Switzerland (2.9%/5.8%) [24], the Netherlands (0.2%/0.3%) [25], the Czech Republic (0.4%/1.1%) [26], the United Kingdom (4.4%/5.9%) [27], Ireland (1.5%/2.5%) [28], Greece (1.1%/9.2%) [29], Italy (8.9%/39.8) [22], Spain (6.5%/53.7%) [30], Romania (-/12.8%) [31], and France (13.2%/9.5%) [32]. Furthermore, there have been rare reports of autochthonous infections with T. equi in two horses in the Netherlands [16], one horse in Austria [33], and in Germany for one [34] as well as three horses [33].…”
Section: Introductionmentioning
confidence: 99%
“…equi have been reported in horses in the Netherlands (0.0%/1.6%) [16], Poland (-/7.2%) [17], Hungary (0.0%/15.1%) [18], Romania (2.2%/20.3%) [19], the central Balkans (2.1%/22.5%) [20], Croatia (3.6%/13.2%) [21], and Italy (10.3%/70.3%) [22]. There have also been reports of seropositive horses in central Germany (0.3%/6.1%) [23], Switzerland (2.9%/5.8%) [24], the Netherlands (0.2%/0.3%) [25], the Czech Republic (0.4%/1.1%) [26], the United Kingdom (4.4%/5.9%) [27], Ireland (1.5%/2.5%) [28], Greece (1.1%/9.2%) [29], Italy (8.9%/39.8) [22], Spain (6.5%/53.7%) [30], Romania (-/12.8%) [31], and France (13.2%/9.5%) [32]. Furthermore, there have been rare reports of autochthonous infections with T. equi in two horses in the Netherlands [16], one horse in Austria [33], and in Germany for one [34] as well as three horses [33].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, comparing PYLL between counties in Romania can help in understanding the impact of certain health issues and diseases on different regions. For example, studies have shown variations in the prevalence of mosquito-borne pathogens and zoonotic diseases in different regions of Romania [ 3 , 4 , 5 ]. By comparing PYLL, it becomes possible to assess the impact of these diseases on premature mortality and prioritize public health measures accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…Data from The Food and Agricultural Organization of the United Nations suggests that approximately 90% of the global horse population resides in EP-endemic areas [3]. EP is common in subtropical and tropical areas of the world and is known to be endemic in several countries in Africa, Asia, the Americas and Europe [4][5][6]. The disease can cause mild subclinical to severe acute clinical signs.…”
Section: Introductionmentioning
confidence: 99%